Public Services and Spatial Justice in Bavarian spatial planning policy: Reflections in light of the foundational economy approach - Dudek, Simon; Zademach, Hans-Martin; Miosga, Manfred (Raumforschung und Raumordnung | Spatial Research and Planning, 2023)
The paper discusses the connection of the foundational economy approach, a contemporary concept in the public services discourse, with the notion of spatial justice. It argues that the economic relevance of the systems of the foundational economy are important for territorial development issues, too and that they are able to provide a substantial contribution to sustainable and just spatial development. First, the concept of spatial justice is introduced as a spatial planning policy interpretation of equal living conditions. Based on four sub-dimensions, it is shown that access to basic services for all people plays an elementary part in this. The concept shares this perspective with the foundational economy approach. The latter opens up a new perspective on public services and, in addition to the service provision, also emphasises the high significance of foundational economic systems for labour markets. Against this background, a descriptive-statistical evaluation of labour market data on the spatial distribution of the foundational economy at the district level in Bavaria is carried out. Overall, the paper addresses the uneven spatial distribution of the foundational economies and advocates better funding for municipalities in order to achieve spatial justice.